Praksis Penanaman Nilai Local Wisdom Masyarakat Desa Jrahi sebagai Learning Resources IPS - Karim, Abdul (Pascasarjana IAIN Kudus, 2022)
The Practice of Instilling Local Wisdom Values for the Jrahi Village Community as Learning Resourcesof Social Studies. Research with locus in Jrahi Village, Gunungwungkal District, Pati Regency, aims to: 1) analyze the praxis of the value of local wisdom of the people of Jrahi Village; 2) assessing the value of local wisdom of the community as a source of social studies learning. The approach in this study is Participatory Action Research – a participatory action research method aimed at identifying research problems based on the needs of the research subject. Researchers as interventionists, activists, and facilitators. The collected data are analyzed qualitatively. The results showed: 1) The praxis of the value of local wisdom of the people of Jrahi Village – such as Sedekah Bumi, Ngalungi Sapi, Barikan, and Dawuhan – became local wisdom that was preserved; 2) The values of local wisdom of the community as a source of social studies learning with the stages of formulating goals, determining material, and making appropriate learning strategies. Penelitian dengan lokus di Desa Jrahi Kecamatan Gunungwungkal Kabupaten Pati, bertujuan untuk: 1) menganalisis praksis nilai kearifan lokal masyarakat Desa Jrahi; 2) mengkaji nilai kearifan lokal masyarakat sebagai sumber pembelajaran IPS. Pendekatan dalam penelitian ini adalah Participatory Action Research –metode penelitian aksi partisipatoris bertujuan mengidentifikasi problem penelitian berdasar pada kebutuhan dari subjek penelitian. Peneliti sebagai interventionist, aktivis, dan fasilitator. Data yang dikumpulkan dianalisis secara kualitatif. Hasil penelitian menunjukkan: 1) Praksis nilai kearifan lokal masyarakat Desa Jrahi –seperti Sedekah Bumi, Ngalungi Sapi, Barikan, dan Dawuhan– menjadi kearifan lokal yang dilestarikan; 2) Nilai-nilai kearifan lokal masyarakat sebagai sumber pembelajaran IPS dengan tahapan merumuskan tujuan, menentukan materi, dan membuat strategi pembelajaran yang tepat.